Coccidioidomycosis Masquerading as Eosinophilic Ascites - Kourosh Alavi; Pradeep R. Atla; Tahmina Haq; Muhammad Y. Sheikh (Case Reports in Gastrointestinal Medicine)
Endemic to the southwestern parts of the United States, coccidioidomycosis, also known as “Valley Fever,” is a common fungal infection that primarily affects the lungs in both acute and chronic forms. Disseminated coccidioidomycosis is the most severe but very uncommon and usually occurs in immunocompromised individuals. It can affect the central nervous system, bones, joints, skin, and, very rarely, the abdomen. This is the first case report of a patient with coccidioidal dissemination to the peritoneum presenting as eosinophilic ascites (EA). A 27-year-old male presented with acute abdominal pain and distention from ascites. He had eosinophilia of 11.1% with negative testing for stool studies, HIV, and tuberculosis infection. Ascitic fluid exam was remarkable for low serum-ascites albumin gradient (SAAG), PMN count >250/mm3, and eosinophils of 62%. Abdominal imaging showed thickened small bowel and endoscopic testing negative for gastric and small bowel biopsies. He was treated empirically for spontaneous bacterial peritonitis, but no definitive diagnosis could be made until coccidioidal serology returned positive. We noted complete resolution of symptoms with oral fluconazole during outpatient follow-up. Disseminated coccidioidomycosis can present in an atypical fashion and may manifest as peritonitis with low SAAG EA. The finding of EA in an endemic area should raise the suspicion of coccidioidal dissemination.